The Taboo Words Used as Mockery Terms in Deadpool Max Volume 1 Comic by David Lapham - Nor Fatimah; Muhammad Adam; Waladdin Panggabean (Prologue: Journal on Language and Literature, 2019)
This research explores two objectives; 1) to identify the types of address terms found in Deadpool Max volume 1 comic. 2) to describe the taboo words used as mockery terms in Deadpool Max volume 1 comic. The theory used in this research is the sociolinguistics analysis using Wardhaugh’s theory. The methodology employed is qualitative research in which the researcher tried to present the issues descriptively. The data were in the form of utterances, while the dialogue uttered from Deadpool Max volume 1 comic was the primary data source. Then various journal, books and internet to support the data analysis were the secondary data source. The results of this research are stated as follows. Firstly, seven types of address terms are found in the comic. 78 total data appear, there are, First Name (FN), Title Alone (T), Title plus Last Name (TLN), Special Nick Name (SN), Pet Name (PN), Kinship Terms (KT), and Mockery Terms (MT). Secondly, the taboo words used as mockery terms are found, and there are 2 reasons of using taboo words; to show anger and to mock.